2022
DOI: 10.1016/j.drugalcdep.2021.109263
|View full text |Cite
|
Sign up to set email alerts
|

Examining the impact of the first wave of COVID-19 and associated control measures on interventions to prevent blood-borne viruses among people who inject drugs in Scotland: an interrupted time series study

Abstract: Background COVID-19 has likely affected the delivery of interventions to prevent blood-borne viruses (BBVs) among people who inject drugs (PWID). We examined the impact of the first wave of COVID-19 in Scotland on: 1) needle and syringe provision (NSP), 2) opioid agonist therapy (OAT) and 3) BBV testing. Methods An interrupted time series study design; 23rd March 2020 (date of the first ‘lockdown’) was chosen as the key date. Results The numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…Changes in the utilisation of harm reduction services following pandemic-related closures and reopenings have been reported elsewhere, with service utilisation not always recovering to pre-pandemic levels ( Trayner et al, 2022 ). In the context of a disrupted injecting risk environment and increasing overdose rates, this is highly concerning and suggests a need to assess the extent and persistence of changes in SCS utilisation in Montréal.…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…Changes in the utilisation of harm reduction services following pandemic-related closures and reopenings have been reported elsewhere, with service utilisation not always recovering to pre-pandemic levels ( Trayner et al, 2022 ). In the context of a disrupted injecting risk environment and increasing overdose rates, this is highly concerning and suggests a need to assess the extent and persistence of changes in SCS utilisation in Montréal.…”
mentioning
confidence: 79%
“…Observed immediate declines in service visits are attributable to public health measures mandating physical distancing, which reduced service capacity. Barriers to service access due to pandemic-related restrictions, including closures, capacity limitations, reduced hours of operation, have been reported in many settings ( Glick et al, 2020 ; Russell et al, 2021 ; Trayner et al, 2022 ; Whitfield et al, 2020 ). In addition to these service disruptions, SCS clients may have avoided attending in order to minimise their infection risk, particularly given the underlying vulnerabilities many clients face ( Ali et al, 2020 ; Bouck et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Croxford et al's epidemiological study relates to the prepandemic period, and the impact of COVID-19 on HIV among PWID in the UK has yet to be fully established. Testing coverage and surveillance have been severely affected [18], and there have been disruptions to harm reduction services including NSP and drug treatment which must not become the new normal [18,19]. On the flipside, many innovative mitigation measures were implemented to maintain services [18].…”
Section: E D I T O R I a Lmentioning
confidence: 99%
“…Testing coverage and surveillance have been severely affected [18], and there have been disruptions to harm reduction services including NSP and drug treatment which must not become the new normal [18,19]. On the flipside, many innovative mitigation measures were implemented to maintain services [18]. We should capitalise on this momentum to progress not only towards HIV elimination but the prevention of other health issues and social harm among PWID.…”
Section: E D I T O R I a Lmentioning
confidence: 99%
“…Latest drug seizure data reports suggest that the supply of illicit opioids remained stable with some short-term localized disruptions [2], and surveys of people who use opioids have reported that consumption patterns generally have not been affected [3]. Administrative data on opioid use disorder (OUD) treatment showed a decline in service use after the pandemic restrictions, with the rate of new treatment admissions increasing after removal of these measures but below prepandemic levels [4,5]. Nevertheless, there is evidence that people with OUD have had higher rates of COVID-19 infection and worsened health outcomes [6].…”
Section: Opioidsmentioning
confidence: 99%